Sharp Coefficient Bounds for Analytic Functions Related to Bounded Turning Functions - Sudhansu Palei; Madan Mohan Soren; Luminiţa-Ioana Cotîrlǎ; Daniel Breaz (Mathematics)
Let <semantics>B</semantics> denote the class of bounded turning functions <semantics>F</semantics> analytic in the open unit disk, where the image of <semantics>F′(z)</semantics> is contained in the domain <semantics>Ω(z)=coshz+<mstyle scriptlevel="0" displaystyle="true">2z2−z2</mstyle></semantics>. This article determines sharp coefficient bounds, a Fekete–Szegö-type inequality, and second- and third-order Hankel determinants for functions in the class <semantics>B</semantics>. Additionally, we obtain sharp Krushkal and Zalcman functional-type inequalities related to the logarithmic coefficient for functions belonging to <semantics>B</semantics>.